Postmodern Syncretism in Naomi Nye’s Works - ZUHAIR S. EISOUH,; SONIA EISOUH, (International Journal of Psychosocial Rehabilitation, 2020)
In the elastic, fluid, and plural world of postmodernism, religion in its authoritative, traditional, clear-cut sense, along with its strictly-observed rituals, commences to diminish or assumes other syncretic or pluralistic forms. Under postmodernism, one’s view of religion may become hazy as the power of absolute values or truths diminishes. The existence of postmodern, relative truths allows individuals to create their own perception of spirituality. For example, one might completely yield practicing strict religious rites and replace them with more secular ones, or adopt an idiosyncratic form of religion which could pose as an amalgamation of several religious beliefs entwined in one postmodern understanding of what religion is to be to an individual. This paper argues that the characters in Naomi Nye’s works Habibi (1) and 19 Varieties of Gazelle (2) who are set in a postmodern ambience, place religion in a grey area, or combine their inherited religion with other religions adopted from the new cultures they encounter. They allow themselves to accept or waver between their traditional or “official” religion and any forms of religion they are exposed to.